Evaluation of non-steady state condition contribution to the total emissions of residential wood pellet stove. (August 2015) - Venturini, Elisa; Vassura, Ivano; Zanetti, Cristian; Pizzi, Andrea; Toscano, Giuseppe; Passarini, Fabrizio
Abstract: In order to evaluate non-steady phase contribution to the total emissions of a pellet stove in real domestic operations, particulate matter and gaseous emissions were determined separately for different operating conditions, i.e. ignition, partial load, increase in power and nominal load. TSP (Total suspended particulate) was sampled with a dilution system and characterized for TC (total carbon), PAHs (polycyclic aromatic hydrocarbons), the main soluble ions, Ni, As, Cd and Pb. Gas monitoring shows that CO and NO emission factors in ignition phase markedly differ from other operating conditions: NO emission factor is lower, while CO one is much higher, since it is a product of incomplete combustion. Start-up phase emission factors are also higher for TSP, Cd and other products of incomplete combustion, i.e. TC and PAHs. Despite being a non-steady phase, the increase in power phase emission factors appreciably differ from steady state ones only for PAHs. Moreover, the PAHs emitted in non-steady state phases have a higher toxicological burden. In conclusion, in order to evaluate the real impact of pellet stove on the environment, transient conditions should be taken into account. The ignition phase, even though it lasts only 20 min, can significantly contribute to pollutant emission. Highlights: Non-steady state condition contribution to pellet stove emissions was evaluated. Emission factors of CO, TSP, TC, Cd and PAHs are higher for the ignition phase. For increase in power phase only PAH emission factor differs from steady state ones. PAHs emitted in non -steady state phases have a higher toxicological burden.